The Investment Effect of Taxation: Evidence from a Corporate Tax Kink*. (December 2014) - Brockmeyer, Anne
Abstract This paper exploits bunching of firms at a tax kink as quasi‐experimental variation to identify the effect of a tax rate change on investment (reported capital allowances). The idea is that firms with a taxable income slightly above the kink have an incentive to reduce their income to bunch at the kink, and increasing investment is one possible strategy for that. This means that bunching of firms should be accompanied by a spike in investment at the kink. Building on the standard bunching framework, I estimate the frequency distribution of firms around the kink and the share of bunchers with excess investments at the extensive and intensive margins. I apply this approach to administrative tax return data for the universe of UK firms from 2001 to 2007 and show that investment by small firms responds significantly to a tax rate change. I find large and significant spikes in the share of capital investors and median capital costs at the £10, 000 kink. The spikes are larger in 2002–05, when the kink is larger, and for quickly depreciating capital items, which yield larger tax reductions. Different pieces of evidence suggest that the investment spikes are at least partly driven by avoidance and evasion behaviour such as misreporting and claiming capital allowances for personal‐use items.